Kontakty polsko-czeskie na tle literatury psałterzowo-biblijnej - Borowiec, Karolina; Kuźmicki, Marcin; Masłej, Dorota (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2015)
The article makes an attempt to verify the theses concerning the kind of dependence of the Old-Polish Psalms and Psalters from the Czech Psalters. By juxtaposing the Latin texts of Psalms and the Old-Polish and Czech translations (here mainly Psalm 50 from the so-called Page of Medyka and St. Florian’s Psalter), the authors demonstrate that – firstly – the voices from the Page of Medyka are not (as contended by Stanisław Rospond) an evidence of “fine tuning” of the text of Psalm 50 from Kmed to the translation of this Psalm from the remaining Old-Polish Psalters, and they may have been a result of contact of the glossator with the Czech text (in the written or verbalized form); secondly – that the similarities of the Polish and Czech Psalters are not necessarily the result of the difficulties connected with translation into Polish or lack of translator’s professional skills. The conducted analyses justify the thesis that the translator of, for example, St. Florian’s Psalter rather made use of individual words or constructions present in Czech Psalters as successive versions of expressing the same contents; what is more, in some cases the similarities prove to be only apparent.